Digital Transformation and Business Process Modeling: Challenges and Opportunities - Ida Hindarsah (Paspama Institute, 2023)
Digital transformation has become top of the agenda for many organizations looking to increase their efficiency, innovation and competitiveness. Business process modeling becomes a critical foundation in managing this change, enabling organizations to redesign and optimize their processes. This research aims to investigate the impact of digital transformation on business process modeling, focusing on the challenges faced and the opportunities that arise in this context. This research uses a qualitative approach with descriptive methods. The research results show that digital transformation in business process modeling has a positive impact on organizations. Effective system integration, use of automation technology and advanced data analysis have increased operational efficiency and customer engagement. Although there are challenges in overcoming resistance to change and integration of complex systems, effective change management can minimize negative impacts. Opportunities opened up through digital transformation include product innovation, enhanced customer experiences, and more effective internal collaboration. In conclusion, organizations that successfully adopt these changes can gain a competitive advantage and improve their performance in an ever-evolving market.